Pedagogia do esporte: análise do regulamento da competição de futebol dos jogos escolares do Amazonas - Mendonça, Mateus Azevedo (Brasil, 2024)
Sports programs organized for children and young people establish an intrinsic relationship between sports activities, training planning and participation in sports competitions. This environment is perceived as an expanded learning opportunity, driven by young people's interactions with diverse individuals playing specific roles, such as parents and family members, coaches, referees, managers and colleagues. In order to meet the needs of children and young people, many competitions have adapted their organizational structures. In this context, it is essential to carry out studies that characterize the current state of children's sports competitions, particularly in the Amazonas region. Therefore, this study aims to investigate how the State Department of Sports and Leisure (SEDEL) and the State Department of Education and Teaching Quality (SEDUC) promote the Amazonas School Games (JEAS) for children within the scope of football. The research follows a descriptive approach of a qualitative nature, with an analytical focus aimed at organizing and systematizing documentary information from state sports entities. Through documentary analysis and discussion with the literature, on a scale of 1 to 4, in which 1 means more adapted competitions and 4 competitions in a traditional format, JEAS received a score of 3.15±1.8, highlighting the need for more efforts by the State Secretariat for Sports and Leisure (SEDEL) and the State Secretariat for Education and Teaching Quality (SEDUC) to promote competitions adapted to children.